Theoretical and methodological approaches to the understanding of human information security - Калюжний, Ростислав Андрійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Review of Olga Zolotar’s monograph "Information Security of Human Rights: Theory and Practice". It is noted that the author’s theoretical and practical researches are based on the results of systematic, comparative-legal analysis of the domestic, European and other states of information legislation, as well as international legal acts. It is concluded that the monograph has a scientific and practical value for use by both scholars and practitioners in the field of law, security, political science, sociology, psychology, including teachers, students and students of both humanitarian and technical educational institutions, and also other readers interested in information and legal issues.